Assessment of MgO and captured CO2 in deep mixing applications: Electrical properties and environmental impacts - Yizhao Liu; Songyu Liu; Guangyin Du; Yong Yang (Case Studies in Construction Materials)
A novel MgO-mixing column was developed for deep soft soil improvement, utilizing in-situ deep mixing of MgO with soil followed by carbonation and solidification via captured CO2 injection. Its low carbon footprint and rapid reinforcement potential make it promising for ground improvement. However, a simple and cost-effective quality assessment method is lacking. This study evaluated the electrical properties of MgO-mixing columns using electrical resistivity measurements, exploring relationships between resistivity parameters and column properties such as saturation, strength, modulus, CO2 sequestration and uniformity. Microscopic analyses were conducted to elucidate the mechanisms underlying carbonation, solidification, and electrical property changes. The life cycle assessment (LCA) was performed to assess its carbon reduction benefits and energy consumption. The findings reveal that the electrical resistivity decreases rapidly with increasing test frequency, remaining constant at 100 kHz, with the average electrical resistivity being slightly higher in the upper section compared to the lower section. Additionally, electrical resistivity follows a power-law decrease with increasing saturation. Both electrical resistivity and the average formation factor exhibit strong positive correlations with unconfined compressive strength (UCS) and deformation modulus, enabling predictive assessments. Furthermore, CO2 sequestration in MgO-mixing columns is positively correlated with electrical resistivity, and the average anisotropy coefficient of 0.96 indicates good column uniformity. Microstructural analyses identify nesquehonite, dypingite/hydromagnesite, and magnesite as significant contributors to strength enhancement. Depth-related changes in electrical resistivity parameters arise from variations in the amount and distribution of carbonation products, which differently impede current flow. LCA highlights the significant low-carbon advantages of MgO-mixing columns